The Potential Anti-Obesity Effect of Heated Stingless Bee Honey in Mice Fed a High-Carbohydrate High-Fat Diet - Delfita, Rina; Marneli, Diyyan (Iraqi Journal of Science, 2026)
Stingless bee honey (SBH) has been widely recognized for its unique bioactive compounds and potential health benefits, including antioxidant and anti-inflammatory properties. However, the effects of heat processing on SBH's bioactivity, particularly its potential anti-obesity effects, remain inadequately explored. This study aims to evaluate the potential anti-obesity effects of heated SBH in mice fed a high-carbohydrate, high-fat (HCHF) diet. This study utilized 30 male white mice with an average weight of 19.03±1.44 g were randomly divided into six groups (n=5). The animals were divided as follows: Group A (Normal Control): Mice fed a standard laboratory diet with no HCHF diet or SBH supplementation. Group B (HCHF Control): Mice fed an HCHF diet without SBH treatment. Group C (HCHF + Unheated SBH): Mice fed an HCHF diet and supplemented with unheated SBH. Group D (HCHF + Heated SBH at 50°C): Mice fed an HCHF diet and supplemented with SBH heated at 50°C. Group E (HCHF + Heated SBH at 75°C): Mice fed an HCHF diet and supplemented with SBH heated at 75°C. Group F (HCHF + Heated SBH at 90°C): Mice fed an HCHF diet and supplemented with SBH heated at 90°C. Mice were administered honey once daily orally for eight weeks. At the end of treatment, body weight, white adipose tissue accumulation, adipose tissue morphology and histology, blood glucose levels, total cholesterol, triglycerides, and HDL-cholesterol were measured. The results showed that mice fed HCHF without SBH administration had abnormal adipose tissue morphology and histology, while administration of heated SBH, especially at a temperature of 50°C, significantly improved the morphological and histological structure of adipose tissue under normal conditions. Administration of heated SBH also reduced adipose tissue weight, decreased fasting blood glucose levels, and increased lipid profiles. Thus, SBH, particularly when heated at 50°C, as a natural therapeutic agent for managing obesity.